Prospect theory, mitigation and adaptation to climate change. Issue 7 (3rd July 2017) - Osberghaus, Daniel
Abstract : Prospect theory (PT) is a widely accepted theory for decisions under uncertainty. However, so far a systematic application to climate policy (CP) does not exist. One important postulation of PT is that outcomes are perceived as gains or losses, relative to the reference point. When it comes to CP, different decision-makers may have different reference points. For example, one decision-maker perceives the current climate as the reference point whereas another decision-maker may have another one, say climate in 100 years. For the former, climate damages are losses and the benefits of CP are reductions of losses. For the latter, benefits of CP are gains. PT suggests that the former places a higher value in CP than the latter. After a critical review whether and how PT may be applied to CP, the paper systematically presents this and other cases where PT offers new insights into climate-related analyses, notwithstanding the importance of well-known aspects such as discounting, altruism, political and economic costs. It is shown that accounting for PT may contribute to a better understanding of some well-known puzzles in the climate debate, including different preferences for CP amongst individuals and nations, the role of technical vs. financial adaptation, and the apparent preference for hard protection measures in coastal adaptation. Finally, concrete possibilities for empirical research on these effects are proposed.